White Garcinia: the white gold for Ayurvedic medicine - Hom, S.; Vasudeva, R.; Lamers, H.; Ramanatha, V.; Sthapit, B. (2011)
This flyer gives good insight into the value of tropical fruit diversity, how it is maintained and used successfully in the field, and how it contributes to the livelihoods and well-being of many rural households. The ‘Conservation and Sustainable Use of Cultivated and Wild Tropical Fruit Diversity: Promoting Sustainable Livelihoods, Food Security and Ecosystem Services’ project encouraged community and local institution to identify such rare and unique elite material from existing diversity and traditional knowledge system as “a good practice of diversity management” that is further promoted for multiplication of planting materials and sustainable management. This flyer tells the story of White Garcinia. This fruit is very rare, and it is reputed to have medicinal properties. Due to its rarity, the White Garcinia is vulnerable to local extinction and the current supply cannot meet the demand.